Association Between Stunting and Anemia Among Toddlers: Stratified by Characteristic of Family and Immunization Status in Mlonggo District, Jepara Regency - Arwinda Nugraheni; Muflihatul Muniroh; Yora Nindita; Firdaus Wahyudi; Bambang Hariyana (Jurnal Kedokteran Diponegoro, 2023)
Background: The risk of anemia in stunted toddlers is higher than in normal toddlers. There is limited research on anemia in children under 3 years old in the community and there is a need for supporting research to prove the possibility of controlling stunting and anemia together. Previous studies have shown that family characteristics and immunization status are associated with the stunting and anemia.